Karakteristik Pengujian Tegangan Tembus Arus Bolak Balik (Ac) Pada Minyak Kedelai (Soybean Oil) Sebagai Alternatif Isolasi Cair - Hardani, Nanda; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research looks at the comparison of the breakdown voltage between mineral oil and soybean oil as an alternative to liquid insulation.This oil test uses half spare electrodes. The value of breakdown voltage of soybean oil is higher than mineral oil. This research also examined in electrode distance variation, reduction of water content and variations in temperature rise on soybean oil to determine the effect of breakdown voltage. less water level in oil results in a higher breakdown voltage. To be used as an alternative to liquid insulation, it must meet several criteria according to the standard specifications of liquid insulating oil. Soybean oil before reducing in water content has rever several criteria requirements including density and viscosity based on standar SPLN 49-1:1982. While the specifications of breakdown voltage, the pour point and flash point not saturate the criteria as an alternative to liquid insulation. Soybean oil after reducing in water content has met several criteria requirements including breakdown voltage, density and viscosity. Whereas for the specifications of the pour point and flash point do not meet the criteria as an alternative to liquid insulation. Keywords: Liquid insulation, breakdown voltage, Soybean Oil.